PENGELOLAAN SAMPAH DI NAGARI SIRUKAM BERDASARKAN PERATURAN DAERAH KABUAPTEN SOLOK NOMOR 7 TAHUN 2018 TENTANG PENGELOLAAN SAMPAH - Boiziardi AS dan Riski Candra (Normative Jurnal Ilmiah Hukum, 2020)
The implementation of waste management is something that must be done, because waste is a threat to the community that can cause disease, therefore waste management is not only the responsibility of the government but is the responsibility of all people for the creation of a clean and healthy environment in Nagari Sirukam, in Waste Management in Nagari Sirukam Based on Solok District Regulation Number 7 of 2018 concerning Waste Management. The formulation of the problem in this study is how waste management in Nagari Sirukam is based on Solok District Regulation Number 7 of 2018 concerning waste management, what are the obstacles and how to overcome obstacles to waste management in Nagari Sirukam Based on Solok District Regulation Number 7 of 2018 concerning waste management. The research method used is juridical impirical is an approach that is done by looking at and gathering all information related to reality in practice in the field. Data collection techniques used were interviews, literature study, and document study. Data processing techniques used are editing, coding, and tabulating, and then the data is analyzed in a qualitative manner, the intention is to analyze not to use numbers but to use sentence descriptions in accordance with the problem formulation which eventually becomes a conclusion. The results of research conducted on waste management in Nagari Sirukam based on Solok District Regulation Number 7 of 2018 on waste management found that the waste management carried out only reached the TPS and did the burning of garbage that had accumulated in the TPS, while the obstacles encountered were not yet the establishment of binding regulations, the absence of landfills, and the lack of waste management transportation tools, how to overcome obstacles that are carried out by establishing village regulations, the existence of a landfill, and adding to the waste management transportation equipment.